2020
DOI: 10.1177/1071181320641094
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in Collaborative Vulnerability Research Workflows

Abstract: Recently, cyber reasoning systems demonstrated near-human performance characteristics when they autonomously identified, proved, and mitigated vulnerabilities in software during a competitive event. New research seeks to augment human vulnerability research teams with cyber reasoning system teammates in collaborative work environments. However, the literature lacks a concrete understanding of vulnerability research workflows and practices, limiting designers’, engineers’, and researchers’ ability to successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It is a cycle that repeats as new leads for investigation are identified or removed from scope. Instead of a 3-phase process with clear milestones and transitions [11], we observed a range of process states that are visited frequently and iteratively during a given RE task, with little indication of how much progress the analyst was making toward a larger goal. Moreover, there was a high degree of variation across participants and their process sequences, indicating that the RE process is less formal or organized than previous representations suggest [11].…”
Section: Rq3: Automatable Tasksmentioning
confidence: 90%
See 2 more Smart Citations
“…It is a cycle that repeats as new leads for investigation are identified or removed from scope. Instead of a 3-phase process with clear milestones and transitions [11], we observed a range of process states that are visited frequently and iteratively during a given RE task, with little indication of how much progress the analyst was making toward a larger goal. Moreover, there was a high degree of variation across participants and their process sequences, indicating that the RE process is less formal or organized than previous representations suggest [11].…”
Section: Rq3: Automatable Tasksmentioning
confidence: 90%
“…Tilley et al identified 3 phases of data gathering, knowledge generation, and information exploration [10]. These studies generalize across types of RE tasks, while Mullins et al focused on defining these phases for a specific RE task [11]. They identified 3 phases in vulnerability discovery: reconnaissance, analysis, and patch & proof.…”
Section: Background and Prior Workmentioning
confidence: 99%
See 1 more Smart Citation